Population Distribution of Amorphophallus at Several Altitudes in Mount Poteng, Raya Pasi Nature Reserve, West Kalimantan - Reine Suci Wulandari; Selvia Ivo; Herlina Darwati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Amorphophallus is a protected and endangered plant. Some Amorphophallus species can only grow in certain environmental conditions. Differences in environmental conditions could cause differences in morphology and distribution of Amorphophallus. This study aimed to obtain the morphological characteristics of Amorphophallus and study the distribution of its population at several altitudes in Mount Poteng, Raya Pasi Nature Reserve, West Kalimantan. The study used an exploratory survey following the river's flow at the Raya Pasi Nature Reserve, especially in Mount Poteng. The results found three species of Amorphophallus: Amorphophallus borneensis (109 individuals), Amorphophallus gigas (9 individuals), and Amorphophallus hewittii (27 individuals), showing clustered distribution patterns with a Morista index of > 1. The similarity index of six comparisons for each altitude showed five altitudes with similar categories and one altitude with a very different category. The results revealed that the Amorphophallus distribution positively correlated with air temperature and soil temperature but negatively correlated with air humidity. However, all correlations were weak. The morphological differences of the three Amorphophallus species were in the forms of the stem pattern, stem height, and fruit shape. The distribution of Amorphophallus can be found at an altitude of 200 − > 500 masl, which is not far from the river flow. Keywords: altitude, Amorphophallus, Mount Poteng, Raya Pasi Nature Reserve